RELAÇÃO ENTRE CARACTERÍSTICAS FENOTÍPICAS E DESEMPENHO REPRODUTIVO DE NOVILHAS NELORES - OLIVEIRA, Matheus Lorrah Costa de; SILVA, Guilherme Baroni da; FERRAZ, André Luiz Julien (ANAIS DO ENIC, 2023)
-